1998
DOI: 10.1111/j.1600-0471.1998.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for specialised ceramic production and exchange in the southeast Arabian Iron Age

Abstract: Results from a programme of PIXE‐PIGME analysis of Iron Age ceramics from southeastern Arabia are presented. Compositional analysis indicates the existence of two discrete Iron Age II ceramic assemblages. A combination of geological and archaeological evidence suggests that one of these was produced in the inland oasis of al‐Ain. Geological evidence in combination with previously published data on the elemental composition of southeast Iranian ceramics suggests Iran as a possible source for the other group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…al‐Madam, Muwailah, Kalba, Husn Madhab and Rafaq) through regional trade systems (Benoist : 363–370). A similar hypothesis was proposed in 1998 by Magee et al based on PIXE‐PIGME analysis of seven samples from the surface of Bida bint Sa'ud in the oasis of Al Ain (Magee et al : table 1).…”
Section: Sandy Buff Waresupporting
confidence: 71%
See 1 more Smart Citation
“…al‐Madam, Muwailah, Kalba, Husn Madhab and Rafaq) through regional trade systems (Benoist : 363–370). A similar hypothesis was proposed in 1998 by Magee et al based on PIXE‐PIGME analysis of seven samples from the surface of Bida bint Sa'ud in the oasis of Al Ain (Magee et al : table 1).…”
Section: Sandy Buff Waresupporting
confidence: 71%
“…Fine red painted ware is found on many sites of the region, from central Oman (Salut, Lizq) to the northern end of the United Arab Emirates (Khatt). In 1998 Magee et al proposed the hypothesis of an Iranian origin for this group, based on stylistic comparisons and on PIXE‐PIGME chemical analyses of six samples which, in composition, were found to be similar to samples of fine grey pottery of the Bronze Age that were analysed in 1989 by Blackman, Méry and Wright, who at the time concluded that an Iranian origin was probable (Magee et al : 243; Blackman, Méry & Wright : table 2). This grey pottery, however, has since been shown to come from Kech Makran in south‐west Pakistan (Blackman & Méry 1999: fig.…”
Section: Fine Red Painted Warementioning
confidence: 99%
“…This very specifi c architectural building, which was visibly a key place in the organization of each Iron Age village of the whole Oman peninsula, was offi cially reported in the scientifi c records for the fi rst time at Rumeilah (Boucharlat & Lombard, 2001a;Magee, 2003). Other artefacts found on site confi rm the existence of long trade links (either direct or mediated) between Rumeilah (and al-Ain oasis at large) with other locations such the Oman peninsula, Bahrain, Mesopotamia, and Iran (Lombard, 1998;Magee, et al, 1998;Magee, 2002).…”
Section: Stakeholder Participation and Values Assessmentmentioning
confidence: 81%
“…Ware with medium to high density of small mineral grits. (28). The samples were prepared at the NWG Macintosh Centre for Quaternary Dating at the University of Sydney using protocols that have been described in previous publications (29).…”
Section: Tepe Yahya Ty390mentioning
confidence: 99%